Management of Acute Wilsonian Hepatitis with Severe Hemolysis: A Successful Combination of Chelation and MARS Dialysis - Jeremy Hassoun; Nathalie Hammer; Giulia Magini; Belen Ponte; Marie Ongaro; Anne-Laure Rougemont; Nicolas Goossens; Jean-Louis Frossard; Laurent Spahr (Case Reports in Hepatology)
Wilson’s disease is a rare hereditary disorder of copper metabolism leading to progressive accumulation of copper in several organs including the brain and the liver. Acute liver failure is a relatively rare hepatic manifestation of WD which may require urgent liver transplantation if medical treatment fails. We report here the case of a young woman who presented with classic acute Wilsonian hepatitis complicated by liver and renal failure and a severe hemolysis related to massive nonceruloplasmin bound copper accumulation requiring repeated blood transfusions. The early initiation of a combined treatment including conventional chelation therapy and repeated MARS dialysis sessions allowed a rapid control of hemolysis, a progressive decrease of free copper overload, and clinical recompensation without liver transplantation.